Diabetic Self-Management and Correlated Factors: A Cross-Sectional Study - Fatharani, Lukman Faishal; Anggraheny, Hema Dewi; Putro, Wahyu Gito (South East Asia Nursing Research, 2024)
Prevention of diabetes complications has an important role in decreasing mortality and morbidity in diabetes patients. Self-management in diabetic patients (DSM) is a recommended strategy to increase the quality of life in diabetes patients. Several factors are related to self-management in diabetic patients. This study aims to discover factors related to self-management in diabetic patients. This is a cross-sectional study performed on 42 diabetic patients. Respondents were given a Diabetes Knowledge Questionnaire (DKQ-24) and a self-management behaviour questionnaire in Diabetes Mellitus (SMDM). Data was analyzed using SPSS version 26. This study had no significant relation between age and self-management (p = 0.987). There was also no statistically significant relationship between gender, education level, and knowledge level with p-value of 0.651, 0.559, and 0.558, respectively. Moreover, there was no correlation between participation in chronic disease management programs and self-management with p = 0.559. This study concluded no correlation between age, gender, education level, knowledge level, and participation in chronic disease management programs with self-management of diabetic patients.